Structural and quantum chemical analysis of exciton coupling in homo- and heteroaggregate stacks of merocyanines - David Bialas (Nature Portfolio, 2016)
Exciton coupling between organic dyes is important for opto-electronic and photovoltaic devices and it is well-known that strong coupling occurs between equal chromophores. Here, Würthner and others show quadruple dye stacks that have strong exciton coupling between different chromophores within a heteroaggregate.